Etika Berkomunikasi Dalam Islam (Kajian Dalam Surat Al-Ahzab Ayat 32 Dan Ayat 70) - Ira Trisnawati; Muhammad Syahrul Mubarak (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang Indonesia, 2020)
Communication is a human need in every activity. Especially in muamalah, communication was an important role in the success and failure of these muamalah activities. Good communication can foster friendship and affection between humans. Ethics is a science that discusses the pros and cons of a human's behavior, human habits in his association with each other. Communication is the process of delivering a message or delivery of information which the meaning of the message’s sender to the recipient of the message, which is used as a tool to achieve certain goals. The ethics of Islamic communication is the procedure in conducting communication in accordance with moral values ​​in determining the good and bad behavior of a person by means of Islamic delivery, so that it leads to the benefit of humanity. This research uses library research method (literature) which focuses on searching and studying literature and other library materials by using qualitative methods and focusing the discussion on Surah al-Ahzab verse 32 and verse 70. Surah Al-Ahzab was a Madaniyah letter which discussing various legal issues, one of which is about the ethics of communication. Ethics in communication should be use qoulan karima and qoulan sadidan which are the teachings of Islam. Ethics taught in Surah al-Ahzab verse 32 and verse 70 teach us that in interacting we must use good ethics, especially in terms of communication, so as not to cause misinterpretation due to poor communication ethics.